Global connections and the structure of skills in local co-worker networks - László Lőrincz; Guilherme Kenji Chihaya; Anikó Hannák; Dávid Takács; Balázs Lengyel; Rikard Eriksson (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2020)
Social connections that reach distant places are advantageous for individuals and firms by providing access to new skills and knowledge. However, systematic evidence on how firms work up global knowledge access is still missing. In this paper, we analyse how global work connections relate to differences in the skill composition of employees within companies. We gather survey data from 10% of workers in a local industry in Sweden and complement this with digital trace data to map co-worker networks and skill composition. This unique combination of data and features allows us to quantify global connections of employees and measure the degree of skill-similarity and skill-relatedness to co-workers. We find that the workers with extensive local networks typically have related skills to others in the region and to their co-workers. Workers with more global ties typically bring in less related skills to the region. These results provide new insights to the composition of skills within knowledge intensive firms by connecting the geography of networks contacts to the diversity of skills accessible through them.
Keywords: D85; J24; J61; 330; Co-worker networks; skills; relatedness; global connections; survey; online social network